2018
DOI: 10.1287/mnsc.2016.2664
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Tendency to Engage in Self-Employment

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(103 citation statements)
references
References 102 publications
0
93
10
Order By: Relevance
“…Specifically, research on the biological or physiological factors that augment or dampen entrepreneurial motivation is largely absent. This is a noteworthy oversight as sleep (Murnieks et al, in press; Barnes, ; Barnes, Miller, & Bostock, ; Gunia, ), testosterone (Nicolaou, Patel, & Wolfe, ), and cortisol levels (Liu‐Qin, Bauer, Johnson, Groer, & Salomon, ; Sherman, Lemer, Josephs, Renshon, & Gross, ) represent factors that may explain meaningful variance in entrepreneurial motivation and draw increasing interest in the OB literature but are understudied in entrepreneurship. More theory and measurement of these individual variables could expand our understanding of the role of physiology in entrepreneurial motivation and also contribute to the OB literature.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research on the biological or physiological factors that augment or dampen entrepreneurial motivation is largely absent. This is a noteworthy oversight as sleep (Murnieks et al, in press; Barnes, ; Barnes, Miller, & Bostock, ; Gunia, ), testosterone (Nicolaou, Patel, & Wolfe, ), and cortisol levels (Liu‐Qin, Bauer, Johnson, Groer, & Salomon, ; Sherman, Lemer, Josephs, Renshon, & Gross, ) represent factors that may explain meaningful variance in entrepreneurial motivation and draw increasing interest in the OB literature but are understudied in entrepreneurship. More theory and measurement of these individual variables could expand our understanding of the role of physiology in entrepreneurial motivation and also contribute to the OB literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some have also found that attention deficit hyperactivity disorder (ADHD) and the associated genes are linked to being an entrepreneur (Mannuzza et al 1993;Nicolaou et al 2011) while others have focused especially on the testosterone levels of individuals and entrepreneurship (e.g. Nicolaou et al 2018;Greene et al 2014;White et al 2006). This strain of literature emphasizes (directly or indirectly) that the entrepreneurial tendency is therefore largely heritable and by nature fixed.…”
Section: The Whole Worldmentioning
confidence: 99%
“…The evidence is not conclusive, though. A more robust finding is that individuals with high testosterone levels have a higher probability to be self-employed (Greene et al, 2014;Nicolaou et al, 2017;Sapienza et al, 2009).…”
Section: Existing Literaturementioning
confidence: 99%